SURVIVAL IN PATIENTS WITH HISTOLOGIC VARIANTS OF UROTHELIAL TYPE BLADDER CANCER - Hartanto, Richard; Pramod, Sawkar Vijay (Indonesian Urological Association, 2024)
Objective: This study aims to determine the life expectancy of patients with histologic variants in urothelial type bladder cancer and the highest or lowest mortality rate in Hasan Sadikin Academic Medical Centre. Material & Methods: A cross-sectional study with total sampling. The samples in this study were patients with histologic variants of urothelial cell carcinoma bladder who received treatment at Hasan Sadikin Academic Medical Centre during the period of 2011 to 2022. Results: A total of 470 patients with a diagnosis of urothelial bladder cancer, 62 patients (13.19%) with histologic variants of urothelial bladder cancer treated with radical cystectomy or TURBT + intravesical chemotherapy at Hasan Sadikin Academic Medical Centre. The highest survival rate was in patients diagnosed with giant cell (66.7%) followed by small cell (50%) and glandular differentiation (40.0%). The 5-yearr survival rate of patients treated with radical cystectomy alone had a higher survival rate of 75.3% followed by radical cystectomy and adjuvant therapy, which was 75.2%. Conclusion: Histologic variants of bladder carcinoma that have the highest mortality rate are tropoblastic differentiation, nested type, micropappilary, and sarcomatoid with the lowest survival rate of 0%. Also, histologic variant of bladder carcinoma that has the lowest mortality rate is giant cell with a survival rate of 66.7%. Keywords: Bladder carcinoma, chemotherapy, trophoblastic differentiation.